Mid- and long-term clinical outcomes of corrective fusion surgery which did not achieve sufficient pelvic incidence minus lumbar lordosis value for adult spinal deformity. Issue 2 (December 2015) - Yamada, Kentaro; Abe, Yuichiro; Yanagibashi, Yasushi; Hyakumachi, Takahiko; Satoh, Shigenobu
Abstract Background Recent studies have demonstrated sagittal spinal balance was more important than coronal balance in terms of clinical result of surgery for adult spinal deformity. Notably, Schwab reported that one of the target spinopelvic parameters for corrective surgery was that pelvic incidence (PI) minus lumbar lordosis (LL) should be within +/- 10 °. The present study aimed to investigate whether the clinical outcome of corrective fusion surgery was really poor for patients who could not acquire sufficient PI-LL value through the surgery. Methods The present study included 13 patients (mean 68.5 yrs old) with adult spinal deformity. Inclusion criteria were corrective fusion surgery more than 4 intervertebral levels, PI-LL ≥10° on the whole spine X-ray immediately after surgery, and follow-up period ≥3 years. All surgeries were performed by posterior approach. Parameters using SRS-Schwab classification, proximal junctional kyphosis (PJK) of ≥15°, implants loosening, and non-union were investigated using the total standing spinal X-ray. Clinical outcomes were evaluated by Japanese Orthopaedic Association scores (JOA score), Oswestry Disability Index, SF-36, Visual Analog Scale for low back pain, and satisfaction for surgery using SRS-22 questionnaire. Results All patients showed the PI-LL ≥20° before surgery. Although the LL were acquired mean 23.6° after surgery, significant loss of correction was observed at final follow up. The acquired coronal spinal alignment was maintained within the follow-up period. However, sagittal vertical axis (SVA) was shifted forward significantly, from mean 4.5cm immediately after surgery to 11.1cm at final follow-up. Five patients showed PJK, 10 patients showed implants loosening, 8 patients showed non-union at final follow-up. The JOA score and mental health summary measures of SF-36 were significantly improved at final follow-up. The satisfaction score was mean 3.3 points, including 3 patients with ≥4 points, at final follow-up. The satisfaction score correlated negatively with SVA at final follow-up (ρ=-0.58 p=0.03). Conclusions The forward shift of SVA was frequently observed, and SVA at final follow-up related to the patient's satisfaction of surgery. This study indicated the importance of postoperative PI-LL value, but also noted 23% of patients acquired good SVA and satisfaction nevertheless they had inadequate postoperative LL.